Capacity of Solid Waste Management of the Municipalities in North-West Region of Bangladesh: A Far Cry with Sustainable Development - A K M Mahmudul Haque; S M Akram Ullah; Md. Asfaq Salehin (UIN Sunan Gunung Djati, 2021)
The study addresses the overall waste management and drainage system of the Municipalities of Bangladesh. It also endeavors to compare the existing system with the requirements of making a sustainable city following the targets of SDG. It tries to highlight the shortcomings of the existing system of waste management and argues that this is never able to confine sustainability in the environment and the habitats of the Municipalities. The study is empirical in nature mainly based on primary data. Data have been collected from the officials and stakeholders of the three selected Municipalities of a North-west district of Bangladesh- Rajshahi through face to face interview and Focus Group Discussion. This paper identifies the fragile solid waste management capacity of the Municipalities of Bangladesh and argues that current practice is nothing but an inevitable setback for the country to achieve sustainable development.